Muslim rulers and rebels : everyday politics and armed separatism in the southern Philippines - McKenna, Thomas M., 1952- (University of California Press, 1998)
In this account of the Muslim separatist rebellion in the Philippines, Thomas McKenna challenges prevailing anthropological analyses of nationalism as well as their underlying assumptions about the interplay of culture and power. He examines Muslim separatism against a background of more than four hundred years of political relations among indigenous Muslim rulers, their subjects, and external powers seeking the subjugation of Philippine Muslims.
Keywords: Moro National Liberation Front.; Moro National Liberation Front; Cotabato City Region (Philippines) -- Politics and government.; Muslims -- Philippines -- Cotabato City Region.; Mindanao Island (Philippines) -- History -- Autonomy and independence movements.; Muslims -- Philippines -- Mindanao Island -- Politics and government.; Mindanao (Philippines : Île) -- Histoire -- Autonomie et mouvements indépendantistes.; HISTORY.; SOCIAL SCIENCE / Anthropology / Cultural & Social; Autonomy and independence movements; Muslims; Muslims -- Politics and government; Politics and government; Philippines -- Cotabato City Region; Philippines -- Mindanao Island; East Asia.; Regions & Countries - Asia & the Middle East.; History & Archaeology.; History